Characteristics of Pregnant Women With Postdate At Rs. Setio Husodo Kisaran - Selvi Puspan Sari; Ririn Anggriani; Henny Ilfa Sari Panjaitan; Luluk Khusnul Dwihestie; Ilma Widiya Sari (Jurnal EduHealth, 2023)
According to the World Health Organization (WHO) in 2010, confirmed every year around the world 358,000 mothers die during pregnancy or childbirth of which 355,000 mothers (99%) are from developing countries. The maternal mortality ratio in developing countries is the highest ranking with 290 maternal deaths per 100,000 live births when compared to the maternal mortality ratio in developed countries, which is 14 maternal deaths per 100,000 live births. Late pregnancy is a pregnancy that goes beyond the age of 294 days (42 weeks) with all its possible complications. Nama lain kehamilan lewat waktu adalah kehamilan serotinus, prolonged pregnancy, atau post – term pregnancy ( Ida Ayu Chandranita Manuaba, dkk, 2017). Defenisioperasional is the definition of variables that will be studied operationally in the field. The variables studied are age, parity, occupation, and the data used is secondary data that is data obtained from data collection by the method of medical Record documentation. The population and sample in this study are pregnant women with postdates of 83 people. Based on the results found pregnant women with postdate menurutusia> 35 known as many as 34 cases ( 40.9 %) and the majority of pregnant women with postdate at the age of 20-35 years as many as 21 cases (25.3 %). Based on parity in perby the majority of pregnant women with postdate pada parity primiparous as many as 25 cases (30.3%) and a minority of pregnant women with postdate pada parity skundipara as many as 18 cases (21.6 %). Based on the work obtained the majority of pregnant women with postdate of IRT work as many as 31 cases ( 37.4 %) and a minority of pregnant women with postdate of civil servants as many as 24 cases ( 28.9 %).